Fabrication of Organic Hec Nanocomposites Modified with Lysine as a Potential Adsorbent for Bilirubin Removal - Li, Chan; Zhang, Wen; Yang, Ning; Zhang, Qing Song (Applied biochemistry and biotechnology, 2019)
As one of the typical phyllosilicate clays, hectorite (Hec) has some excellent characteristics and has been greatly applied in adsorption field for the removal of dye, endotoxin, etc. In this study, organic Hec nanocomposites modified with l -Lysine (Lys/Hec NCs) were prepared via solution intercalation method for BR removal. The effects of ionic strength, pH values, initial concentration of BR, and BSA concentration on the adsorption capacity for BR of Lys/Hec NCs were investigated. Results indicated that the adsorption capacity for BR of nanocomposites could reach 40 mg/g when the initial bilirubin concentration was 200 mg/L. However, the adsorption amount of Lys/Hec NCs decreased with increasing the concentration of BSA, but Lys/Hec NCs could still maintain a higher adsorption rate. The adsorption kinetics and adsorption isotherms indicated that the adsorption process of Lys/Hec NCs agreed well with the pseudo-second-order model and the Langmuir isotherm, respectively. Moreover, Lys/Hec NCs also exhibited excellent cytocompatibility. These obtained results demonstrate that Lys/Hec NCs prepared in this study had great potential to be used in hemoperfusion.